2014
DOI: 10.1111/jre.12245
|View full text |Cite
|
Sign up to set email alerts
|

Enamel matrix derivative, inflammation and soft tissue wound healing

Abstract: Over 15 years have now passed since enamel matrix derivative (EMD) emerged as an agent capable of periodontal regeneration. Following thorough investigation, evidenced-based clinical application is now established for a multitude of clinical settings to promote regeneration of periodontal hard tissues. Despite the large number of studies and review articles written on this topic, no single review has compiled the influence of EMD on tissue inflammation, an area of research that merits substantial attention in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 94 publications
(217 reference statements)
2
57
0
4
Order By: Relevance
“…The literature suggests that roughly 30% of PDLCs retain the potential to differentiate into cells with osteoblastic properties . To stimulate and enhance this differentiation process, several substances have been tested, ranging from bone‐like materials (eg, hydroxyapatite), to vitamins, polypeptides, and proteins (eg, enamel matrix derivatives and bone morphogenetic proteins ‐ BMPs) . A recently added candidate to be included in this test‐list is Sr .…”
Section: Discussionmentioning
confidence: 99%
“…The literature suggests that roughly 30% of PDLCs retain the potential to differentiate into cells with osteoblastic properties . To stimulate and enhance this differentiation process, several substances have been tested, ranging from bone‐like materials (eg, hydroxyapatite), to vitamins, polypeptides, and proteins (eg, enamel matrix derivatives and bone morphogenetic proteins ‐ BMPs) . A recently added candidate to be included in this test‐list is Sr .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, EMD has been shown to increase the OPG/RANKL ratio in osteoblast cultures and subsequently inhibit osteoclast formation in vitro , which may reduce local bone resorption and favour bone formation (Miron et al. ). This study revealed that gaining bone from baseline to the 12‐month follow‐up was associated with EMD treatment and a Gram+/aerobic bacterial flora, which indicate a possible role of EMD on both bone regeneration and microflora in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…; Miron et al. ,b,c). Amelogenins, the major components of EMD, are a family of hydrophobic proteins that account for over 90% of the total protein content (Lyngstadaas et al.…”
mentioning
confidence: 96%
“…For these reasons, the combination of EMD with various bone grafting materials has been utilized to improve both hard and soft tissue regeneration (Miron et al. ,b,c; Matarasso et al. ).…”
mentioning
confidence: 99%